Fuzzy Set Theory and Topological Games over Some Rectangular Product Spaces and Its Fuzzification - Anand Kumar Singh, (International Journal of Scientific Research in Science and Technology, 2025)
In this paper we present fuzzy sets theory and topological games over some rectangular product spaces and its fuzzification. By introducing the concept of topological game over an ideal of topological space, a game over some rectangular product is played. Fuzzy set theory has been applied to fuzzified some of the results obtained.
Keywords: Fuzzy set theory; Topological space; Game theory; Core and stable sets